Warning Time Analysis of Nasiri River Flash Flood due to Several Possible Natural Dam Break Events - Andry Putra Styawan; Adam Pamudji Rahardjo; Joko Sujono (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2018)
Flash flood disasters caused by natural dam break have already occurred several times in Indonesia which contributes so much life loss and material damage. This research was aimed to study threat level on flash food disasters on the possibility of the locations where the natural dam was formed by the landslide on the river cliffs at the watershed. The flash flood in Nasiri River on August 1st, 2012 would be used for the model in this research. Therefore, hydrology and hydraulic simulations would be conducted on the process of natural dam break at specified altitudes which were predicted to occur in five locations along the Nasiri River. Several big rain event data sets that could occur on specified years from the previous studies would be used to obtain rain event with the hydrological model. Natural dam break was modeled with HEC-HMS 4.1. The hydraulic simulation used the dynamic flow model in the HEC-RAS 5.3 software. The natural dam collapse would be approached by considering the event that has existed around the study location, and also the local geological condition. The result showed that for all the natural dam break scenarios, it could be concluded that the storage filling time was in the time range of 2 hours 26 minutes up to 5 minutes. The flood travel time was ranged from 27 minutes to 2 minutes. The available warning time was quite short, which was less than 3 hours; therefore the need of early warning system’s facilities and infrastructure are absolutely necessary as one of mitigation effort for flash flood disaster in Nasiri Village.